Semisynthetic Abietic and Dehydroabietic Acid Derivatives and Triptoquinone Epimers Interfere with LPS-Triggered Activation of Dendritic Cells (2022)
ABSTRACT: Abietic acid (AA), dehydroabietic acid (DHA) and triptoquinones (TQs) are bioactive abietane-type diterpenoids, which are present in many edible vegetables and medicinal herbs with health-promoting properties. Evidence suggests that beneficial effects of diterpenes operate, at least in part, through effects on cells in the immune system. Dendritic cells (DCs) are a key type of leukocyte involved in the initiation and regulation of the immune/inflammatory response and natural or synthetic compounds that modulate DC functions could be potential anti-inflammatory/immunomodulatory agents. Herein, we report the screening of 23 known semisynthetic AA and DHA derivatives, and TQs, synthesized previously by us, in a multi-analyte DC-based assay that detects inhibition of pro-inflammatory cytokine production. Based on the magnitude of the inhibitory effect observed and the number of cytokines inhibited, a variety of activities among compounds were observed, ranging from inactive/weak to very potent inhibitors. Structurally, either alcohol or methyl ester substituents on ring A along with the introduction of aromaticity and oxidation in ring C in the abietane skeleton were found in compounds with higher inhibitory properties. Two DHA derivatives and two TQs exhibited a significant inhibition in all pro-inflammatory cytokines tested and were further investigated. The results confirmed their ability to inhibit, dose dependently, LPS-stimulated expression of the co-stimulatory molecules CD40 and/or CD86 and the production of the pro-inflammatory cytokines IL-1β, IL-6, IL-12 and TNFα. Our results demonstrate that DC maturation process can be targeted by semisynthetic DHA derivatives and TQ epimers and indicate the potential of these compounds as optimizable anti-inflammatory/immunomodulatory agents.